EVALUATION OF SPECTRUM OF LABORATORY HEMATOLOGICAL MANIFESTATIONS IN DENGUE FEVER - Fouzia Zeeshan Khan; Mehwish Sajjad; Huma Mansoori; Hira Qadir; Mona Siddiqui; Sahar Iqbal (LIAQUAT MEDICAL RESEARCH JOURNAL, 2023)
Dengue virus belongs to flavivirus family which gains entry into the host organism through skin following an infected mosquito bite. Humoral, cellular, and innate host immune responses are involved in the progression of the disease. Dengue fever is getting common in Pakistan, and at times shows high mortality, but there is limited literature available. Therefore, this study was designed to evaluate hematological parameters in patients with dengue fever. This was a retrospective cross-sectional study conducted in the Department of Microbiology, Dow Diagnostic Reference and Research Laboratory, Karachi, Pakistan from 1 January 2021 till December 2021. A total of 6140 were collected, out of which 1746 were found positive. Dengue infection was confirmed by rapid screening NS1 antigen by ICT method. IgM antibodies were detected by Enzyme linked immunosorbent assay (ELISA). Hematological analysis was performed on Sysmex analyzer. Among the 1746 positive samples, 1036 (60%) were males and 710 (40%) were females. More than 10 hemoglobin and 45 hematocrits were found in greater than 40% of cases. Leucopenia less than 4000 was observed mostly in age group 0-20 years. Eosinophilia, basophilia, lymphocytosis and atypical lymphocytosis were shown equally in all age groups. Our study found greater incidence of Dengue fever among 21-40 years of age group with male predominance. Hematological spectrum revealed thrombocytopenia, lymphocytosis, high hematocrit, eosinophilia, basophilia and monocytosis at the time of diagnosis.